AN OCCUPIED CHURCH?: READING THE OCCUPY WALL STREET MOVEMENT ECCLESIOLOGICALLY IN CONVERSATION WITH NEW MONASTICS - Buskirk, Gregory P. Van (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2021)
The church needs to challenge itself about its identity, constitution, and mission, because out of necessity this involves the world and the events that unfold in it. Thus, sociological, political, and economic issues have ecclesiological components and consequences that are practically tautological, including the Occupy Wall Street (OWS) movement. The question thus moves from whether the Church is called to critical reflection on OWS to how that critical reflection should occur. The purpose of this article is to point out the specific practice of the OWS movement – ​​the “sign” – to be considered through an ecclesiological lens. The method used is from an ecclesiological lens with a new monastic. The results of this research are firstly, the church must actively and responsibly inculcate non-violent practices, communitarian economy, and embody space and place, while at the same time joining forces with non-ecclesiastical organizations that support these practices. similar. Second, by whom - and by whom - the Church (as a very different polis) must always point beyond itself to what is its foundation and fulfillment. As long as the Church faithfully responds to this call, the Kingdom will be in our midst.